Failure analysis of cylinder head studs of a four stroke marine diesel engine. (July 2019) - Fonte, M.; Reis, L.; Infante, V.; Freitas, M.
Abstract: After about seven years in service, four cylinder head studs, which tight the block and cylinder heads of a marine main engine, have fractured. Meantime, they were changed for new ones without to determine the root cause of failure. The aim of this research work is to carry out a failure analysis in order to avoid recurrent damages in that engine. The fracture morphology and thread roots of fractured studs were carefully observed by optical devices. Thread material defects and corrosion were not found. However, the thread roots, where the stress concentration are higher, can be pointed as the local of fatigue crack initiation. As is well-known, all cylinder head stud bolts are pre-tensioned in order to increase the mean stress σm and reduce the stress amplitude σa . The steel alloy quality and design are of primordial importance for improving the lifetime of studs, and this is supervised by the Classification Societies (CS), as is indicated by an engraved stamp on each stud end, that certifies each one of them. The pre-tightening of the studs was calculated, and results point as root cause of failure a significant high stress concentration mainly at the second thread root of the studs, close to the bottom side of the nut, which are critical stress zones. Highlights: A detailed failure analysis of cylinder head studs of a four stroke marine diesel engine was performed. The importance of the preload on studs and bolts, being pointed as the main root cause of the premature failure. Fatigue process was initiated at the second thread root, which is a critical thread zone. When studs and bolts should be changed by new ones.